Molecular Prevalence Of Babesia Bigemina Infection In Cattle In Western Semi-Arid And Foothill Regions Of Punjab (India) (Applied Biological Research, 2015)
A nested PCR based prevalence study was done from June, 2011 to May,  2013 to determine the carrier status of Babesia bigemina infection in  apparently healthy crossbred cattle from Western semi-arid and Foothill  regions of Punjab (India). Of the 278 blood samples collected, an amplicon  of 170 bp size was detected in 16.19% animals by nested PCR aa compared  to the routine blood smear examination which showed parasitic piroplasms  in only 1.80% samples. Regarding various risk factors, statistically non significant variation was observed with respect to zone-wise, sex-wise and  age-wise prevalence whereas season-wise disease prevalence showed  significant variation (p
Keywords: Babesia bigemina; cattle; nested PCR; prevalence; risk factors